Experiences in teaching Hydrogen Technologies in the framework of the International Campus of Excellence Andalucia TECH - Rodríguez-García, Eduardo Amador; Rosa Iglesias, Manuel Felipe; Pino Lucena, Francisco Javier; Guerra Macho, José J. (My University, 2018)
The increasing importance of hydrogen technologies is demanding prepared professionals in the numerous topics related to this energy vector. Apart from some basic and advanced courses given by actual experts in these topics, universities must play an important role in the general formation of future professionals. In this way, the International Campus of Excellence (ICE) Andalucía TECH has created several degrees taught jointly by its participating universities of Seville (US) and Málaga (UMA). Among those degrees, Energy Engineering is the best suited to the field of this conference because this degree provide future engineers with specialized training in energy generation, transformation and management. In relation to hydrogen technologies this degree includes a cross sectional optional unit named Hydrogen Based Systems (4.5 ECTS/112.5 h), which is placed in the last term of the fourth year and sharing space with work placement and mobility courses. This paper will present some author’s experiences as teachers of that unit during its short history of only three years. In spite of being a joint degree, which is coordinated between both universities (US and UMA) trying to give similar contents, it is interesting to highlight the differential experiences coming from the teachers of both universities in relation to the teaching methodologies and academic results.
Keywords: Hidrógeno - Aplicaciones industriales; Ingeniería industrial - Estudio y enseñanza; Hydrogen; Andalucia TECH; Teaching; Learning